Independence, Dependence, and Intellectual Disability: From Cultural Origins to Useful Application - Danforth, Scot (Philosophical Inquiry in Education, 2021)
American government educational policy and leading advocacy groups commonly espouse independence as a primary goal for young people with intellectual disabilities. An extensive philosophical literature of autonomy has focused mostly on analyses of cognition that achieve individual self-governance. But the loosely defined concept of independence used by disability policymakers and advocates provides a more malleable, social understanding that involves someone actively relying on the assistance of others. The purpose of this paper is to examine the cultural, historical origins of the notion of independence for disabled persons through an exploration of the biography of Ed Roberts, the father of the independent living movement, and the cultural context of Berkeley, California, in the 1960s and 1970s, where the movement began. The paper applies those cultural concepts to the life situations of persons with intellectual disabilities, asking how well independence serves as a useful goal for the group.